Analisis Kebijakan Pada Kebutuhan Transportasi Laut Di Pelabuhan Batu-Guluk Kepualauan Kangean Kecamatan Arjasa Kebupaten Sumenep - Sulala, Anis; Albab, Ulul; Pramudiana, Ika Devy (Institut Riset dan Pengembangan Indonesia, 2023)
In Indonesia there are several types of sea transportation, some of which are commonly used for public purposes. Some are only used for certain purposes. The port itself as a sea transportation infrastructure that supports smooth sea transportation has a function that is closely related to social and economic factors. Batu-Guluk Harbour is a ferry port that connects Kangean Island with Madura Island. Lack of passengers, for example the ship has exceeded its load and capacity but the ship's officers sometimes still accept passengers. This study aims to find out how to analyze the policy on sea transportation needs at Batu Guluk Port and to find out what factors support and hinder the process of sea transportation activities at Batu Guluk Port, according to William dunn. The research method chosen in this study uses a qualitative approach, the data collected is in the form of document data, data interviews, data observation, then analyzed using interactive data analysis. The results obtained are: (1) Lack of sea transportation and passenger comfort Sea transportation for passengers cannot be said to be feasible because of the large passenger capacity and the small size of the ship, this is very dangerous with the safety and comfort of passengers. So sea transportation for passengers provided must be added considering the large number of passengers needed by increasing cooperation between shipping companies and also looking for sponsors to be able to meet the shortage of sea transportation to the Kangean Islands, (2) Supporting factors in the process of sea transportation activities at Batu port-Guluk the availability of several workforces used such as laborers who assist in the process of loading and unloading passengers and ship departure times which are always on time and goods while the inhibiting factors in the process of sea transportation activities at Batu-Guluk port are weather, lack of availability of transportation fleets, and shortage of officers counter in serving the purchase of tickets.